The importance of web activities for computer forensics - Varol, Asaf; Sönmez, Yeşim Ülgen (Institute of Electrical and Electronics Engineers Inc., 2017)
Web activities are big data revealing the thoughts and intentions of users. Every file that is downloaded, and each searching word in the search engine are thought as reflections of the user's tendencies. Web activities are used to analyze in traces of crime in all kinds of information systems such as computers and mobile phones which are electromagnetic optical devices. The use of smart systems or statistical inference models in the electronic evidence analysis will contribute to the development of digital forensic tools and information technology law. The evidence analysis stage will be faster and automatic. The aim is to extract web browsing data by starting from search engine browsing data with appropriate methods, and sort out the data pointing crime by applying various techniques. © 2017 IEEE.
2nd International Conference on Computer Science and Engineering, UBMK 2017 -- 5 October 2017 through 8 October 2017 -- Antalya -- 132116
Keywords: Computer forensics; Web activities; Web browsers